Analisis Fungsi, Peran, dan Kategori Sintaksis pada Teks Cerita dalam Buku Ajar Bahasa Indonesia Kelas VIII SMP Kurikulum Merdeka (International Forum of Researchers and Lecturers, 2023)
The study was created to analyze the function, role, and syntax category in the sentences in story texts used in the Indonesian language textbook for class VIII junior high school independent curriculum. The data analysis technique used in this study is a billing technique with a theoretical language approach that focuses on each of the grammatical elements in sentence formation. The data on this analysis is the function, role, and syntax category in direct sentences and indirect sentences. The data source is two-story texts entitled